Psoriatic arthritis: clinical and ultrasound parallels - I. F. Fairushina; E. R. Kirillova; D. I. Abdulganieva; E. V. Sukhorukova; E. I. Mukhametshina (Современная ревматология, 2020)
Objective: to assess the relationship of the clinical characteristics and laboratory inflammatory markers to the ultrasound signs of synovitis and enthesitis in patients with psoriatic arthritis (PsA).Patients and methods. Examinations were made in 63 patients diagnosed with PsA according to the 2006 Classification Criteria for Psoriatic Arthritis (CASPAR) criteria. Among the patients, the majority were females (54.2%); the mean age was 42.9±10.3 years; the median (Me) PsA duration was 7 [3; 10] years; Me Disease Activity in Psoriatic Arthritis (DAPSA) was 16.5 [11.6; 25] years.All the patients underwent estimation of tender joint count, swollen joint count, tender entheseal count, inter alia using the Leeds Enthesitis Index (LEI), Maastricht Ankylosing Spondylitis Enthesis Score (MASES), and Spondyloarthritis Research Consortium of Canada (SPARCC). The investigators determined PsA activity by DAPSA and the prevalence and severity of psoriasis by the Psoriasis Area and Severity Index (PASI) and also estimated erythrocyte sedimentation rate (ESR) and high-sensitivity CRP (hs-CRP) levels. Ultrasonography was used to assess bilateral upper and lower limb joints, by calculating joint counts (JC) with synovitis signs (SJC), as well as tendon and ligament entheses (a total number of 54 in one patient), by determining the presence of vascularized enthesis count (VEC) and structurally changed enthesis count (SCEC) and using the ultrasound indices (Glasgow Ultrasound Enthesitis Scoring System (GUESS), Belgrade Ultrasound Enthesitis Score (BUSES), Madrid Sonography Enthesitis Index (MASEI), Sonographic Enthesitis Index (SEI)).Results and discussion. There were no significant differences in the frequency of damage to the upper (15.7%) and lower (19.3%) limb joints (p>0.05), whereas inflammation in the entheses of the lower limbs (23.2%) was significantly more common than that in the upper limbs (15.3%) (p<0.01). A weak relationship was established between SPARCC and SEI (r=0.276; p<0.05). A positive correlation was found between VEC and hs-CRP levels (r=0.323, p=0.01), ESR (r=0.332, p<0.01). Ultrasound imaging showed that SJC (p<0.01), enthesitis count (p<0.01), and SCEC (p<0.05) increased with age. The relationship between SCEC and GUESS (r=0.724; p<0.01) and that between the VEC and BUSES (r=0.562, p<0.01) proved to be more pronounced.Conclusion. Ultrasound imaging indicates that the entheses of the lower limbs are more frequently affected in patients with PsA. There is no relationship between DAPSA and ultrasound inflammatory changes in the joints and extra-articular structures. A strong relationship is established between enthesiseal structural and inflammatory changes and GUESS and BUSES, respectively, which allows one to recommend the use of these indices for assessing enthesitis in PsA. Entheseal vascularization associated with inflammatory markers (hs-CRP, ESR) (p<0.05) is a manifestation of PsA activity regardless of age and DAPSA.